THE DEVELOPMENT OF INCLUSIVE EDUCATION MANAGEMENT MODEL TO IMPROVE PRINCIPALS AND TEACHERS PERFORMANCE IN ELEMENTARY SCHOOLS (Universitas Negeri Semarang, 2014)
The purpose of this study was to (1) describe the current condition of implementation of inclusive education in primary schools, (2) to develop a model of inclusive education management, and (3) to examine the effectiveness of the management model of inclusive education in primary schools. Method of Research and Development (R & D) was used in this study, with the following stages: (1) a preliminary study to see the existing implementation of inclusive education in elementary schools through literature review and field study, (2) developing a model of inclusive education management, and (3) examiningÂ the effectiveness of inclusive education management model. This research was conducted in 51 inclusive schools located in four districts namely; Surakarta, Boyolali, Sukoharjo, and Karanganyar. The subject of this research consisted of principals, class teachers, students with special needs education (SNE), students without SNE, and school committee. The results of the preliminary study concluded (1) the use of existing performance indicators principals and teachers, the implementation of inclusive education in primary schools did not meet the expected criteria, (2) one of the most widely perceived obstacle is the unavailability of standardized management of inclusive schools, (3) response of the school committee, students with SNE, and students without SNE to inclusive education category is quite positive, (4) the inclusive schools did not run functions and aspects of school management adequately, (5) the schools urgently needed guide management of inclusive education. The final product of the development of inclusive education management model requires that inclusive schools run the four functions of management; planning, organizing, implementing, and controlling, by combining the nine aspects of school management in terms of institutional management, curriculum, teaching process, evaluation, student, facilities, human resources, public participation and financing. To run the management model of inclusive education effectively, guide book on inclusive education management should be provided. The result of the evaluation by principals and teachers indicated that inclusive education management model was very effective. From the result, it is recommended that the guide book be disseminated for use as a guideline in the management of inclusive education in elementary schools in Indonesia.